High Prevalence of Seasonal and Current Groin Problems in Rink Hockey Players - Quintana-Cepedal, Marcos; de Pablo Marquez, Bernat; del Valle Soto, Miguel; Olmedillas, Hugo (International Journal of Sports Medicine, 2024)
Groin problems are common in multidirectional sports. The aim of the present study is to assess seasonal, current, and trends for groin problems in rink hockey players, irrespective of their playing position, age, or gender. Rink hockey players from three countries [n=446 (162 female, 284 male)] were invited to participate in an online questionnaire. This form evaluated the prevalence of groin problems (time-loss and non-time-loss) for the 2022–2023 season, as well as monthly prevalence of groin problems (time-loss and non-time-loss). All groin problems were compared between playing position, gender, and age to assess between-group differences. Senior males reported the highest time-loss (25%) and non-time-loss (51%) for seasonal prevalence; while U-17 males reported the lowest in both categories of groin problems (time-loss 9%, non-time-loss 27%). No significant differences between playing position or gender were found for any of the groin problems analyzed. In-season prevalence (9–15.7%) of groin problems was significantly higher than pre-season (7.4%) prevalence (p<0.01). Seasonal prevalence of groin problems is common in rink hockey, regardless of gender, playing position, or age. Preventive efforts should be directed towards all players, regardless of their individual characteristics.
Keywords: HAGOS; rink hockey; female athletes; groin pain